Thermodynamic Analysis of a Peak Shaving Power Station based on the Liquid Air Energy Storage System with the Utilization of Liquefied Natural Gas in the Liquefied Natural Gas Terminal. Issue 2 (12th January 2021) - Guo, Luna; Ji, Wei; An, Baolin; Hu, Jianying; Gao, Zhaozhao; Fan, Xiaoyu; Wang, Junjie
Abstract : The integrated system of regasification of liquefied natural gas (LNG) and liquid air energy storage (LAES) has advantages of improving the LAES system efficiency and energy grade matching utilization of the LNG cold energy. But the influence of the cold energy storage efficiency on the combined system is ambiguous and the decoupling mechanism between the energy storage and release processes with the addition of the LNG cold energy was seldom investigated. Thus, a hybrid LAES system using LNG is proposed. The thermodynamic model is established to analyze the system performance. The influence of key parameters on the system and the removal of the coupling effect are originally analyzed. The results show that the electricity storage efficiency ( η ese ) and exergy efficiency ( η exe ) of the typical operational condition can reach 107.3% and 49.4%, respectively. With the cold energy storage efficiency varying from 0% to 100%, the η ese and η exe increase by 18.0% and 4.4% averagely. Furthermore, to investigate the influence mechanism of introducing LNG to the LAES system, the performance of four different systems is compared. With the decoupling between the energy storage and release processes, the η ese is improved obviously and the η exe can be maintained at a high level. Abstract : Herein, a large‐power bidirectional peak shaving power station based on liquid air energy storage is proposed and the influence of the cold energy storage efficiency on the system is analyzed. Comparative analyses of four different systems are carried out. Furthermore, decoupling mechanism between the energy storage and release process with liquefied natural gas (LNG) cold energy is clarified.